Meteorological and Hydrological Data as a Basis for Issuing Flood Warnings During the July Flood 2021 in Rhineland‐Palatinate and North Rhine‐Westphalia (Germany) - Jens Reinert; Elena‐Maria Klopries; Holger Schüttrumpf (Journal of Flood Risk Management, 2025)
ABSTRACT The July 2021 flood event severely affected western Germany, particularly Rhineland‐Palatinate and North Rhine‐Westphalia, with rainfall intensity and water levels exceeding the 100‐year return period in many areas. This study analyzes the performance of flood monitoring and forecasting systems during this extreme event, focusing on the integration of meteorological and hydrological data within detection, monitoring, and forecasting processes. The findings reveal critical challenges in translating meteorological information into actionable flood warnings, including discrepancies between predicted and observed precipitation, underestimation of maximum discharges (exceeding the 100‐year return period by up to 730% in some areas), and the absence of comprehensive flood forecasting systems in key regions. Approximately 60% of the investigated gauging stations experienced exceedances of all defined flood warning thresholds within 6 h or less, highlighting the rapid escalation of the event and the constrained response time for emergency measures. The results of the study underline the need to redesign flood information and warning systems: especially for extreme situations warnings must not be based only on measured data and not on single forecast values but mainly on potential risks and communicated uncertainty/probability.